1975
DOI: 10.1084/jem.142.3.785
|View full text |Cite
|
Sign up to set email alerts
|

Passive transfer of experimental autoimmune myasthenia by lymph node cells in inbred guinea pigs.

Abstract: Passive transfer of experimental autoimmune myasthenia (EAM) was performed with lymph node cells from donor guinea pigs immunized with purified acetylcholine receptor (AChR) from Torpedo californica. Recipient animals revealed the same clinical signs and electromyographic patterns as observed in actively challenged animals. These phenomena are parallel to the clinical manifestations of the human disease myasthenia gravis, in which cellular response to AChR was recently demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1976
1976
1985
1985

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…However, in acute and passive EAMG, a widespread invasion of macrophages occurs at the endplate [49,53,95]. In acute EAMG, macrophages bear cytophilic antibodies specifically directed against AChR [ 108], and passive transfer of lymph node cells from EAMG animals can induce the disease in recipient animals [90,138]. In cultures of rat skeletal muscle cells, an application ofmacrophages from EAMG rats produces cytotoxic effects in 24 to 72 hours [139].…”
Section: Cell-mediated Immunity At Endplatesmentioning
confidence: 99%
“…However, in acute and passive EAMG, a widespread invasion of macrophages occurs at the endplate [49,53,95]. In acute EAMG, macrophages bear cytophilic antibodies specifically directed against AChR [ 108], and passive transfer of lymph node cells from EAMG animals can induce the disease in recipient animals [90,138]. In cultures of rat skeletal muscle cells, an application ofmacrophages from EAMG rats produces cytotoxic effects in 24 to 72 hours [139].…”
Section: Cell-mediated Immunity At Endplatesmentioning
confidence: 99%
“…In 1973 it was shown that immunization of rabbits with the acetylcholine receptor resulted in the development of a disease almost identical to myasthenia gravis (14,24). This disorder can be transferred with lymphocytes (36), whereas a single transfer of antibodies directed to ace tylcholine receptor only induces a transient disease ( 19).…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral T lymphocytes of EAMG-affected animals can be prestimulated in vitro by AcChoR (4,5). AcChoR-specific T lymphocytes from EAMG rats have been shown to be involved in immune responses against AcChoR and in the development of EAMG (5,6).…”
mentioning
confidence: 99%
“…Peripheral T lymphocytes of EAMG-affected animals can be prestimulated in vitro by AcChoR (4,5). AcChoR-specific T lymphocytes from EAMG rats have been shown to be involved in immune responses against AcChoR and in the development of EAMG (5,6). T cells from MG patients proliferate in vitro in the presence of AcChoR (7)(8)(9) and the analysis of T-cell subsets in myasthenics has shown, in several patients, a defect in peripheral T-suppressor cell number (10,11) or an impairment of T-cell suppressor functions (10)(11)(12)(13).…”
mentioning
confidence: 99%